High-resolution array CGH clarifies events occurring on 8p in carcinogenesis - Ellis Ian O; Chin Suet-Feung; Pole Jessica CM; Cooke Susanna L; Caldas Carlos; Edwards Paul AW (BMC Cancer, 2008)
Abstract Background Rearrangement of the short arm of chromosome 8 (8p) is very common in epithelial cancers such as breast cancer. Usually there is an unbalanced translocation breakpoint in 8p12 (29.7 Mb – 38.5 Mb) with loss of distal 8p, sometimes with proximal amplification of 8p11-12. Rearrangements in 8p11-12 have been investigated using high-resolution array CGH, but the first 30 Mb of 8p are less well characterised, although this region contains several proposed tumour suppressor genes. Methods We analysed the whole of 8p by array CGH at tiling-path BAC resolution in 32 breast and six pancreatic cancer cell lines. Regions of recurrent rearrangement distal to 8p12 were further characterised, using regional fosmid arrays. FISH, and quantitative RT-PCR on over 60 breast tumours validated the existence of similar events in primary material. Results We confirmed that 8p is usually lost up to at least 30 Mb, but a few lines showed focal loss or copy number steps within this region. Three regions showed rearrangements common to at least two cases: two regions of recurrent loss and one region of amplification. Loss within 8p23.3 (0 Mb – 2.2 Mb) was found in six cell lines. Of the genes always affected, ARHGEF10 showed a point mutation of the remaining normal copies in the DU4475 cell line. Deletions within 12.7 Mb – 19.1 Mb in 8p22, in two cases, affected TUSC3. A novel amplicon was found within 8p21.3 (19.1 Mb – 23.4 Mb) in two lines and one of 98 tumours. Conclusion The pattern of rearrangements seen on 8p may be a consequence of the high density of potential targets on this chromosome arm, and ARHGEF10 may be a new candidate tumour suppressor gene.